Dampak Penggunaan Alsintan Pada Kondisi Sosial Ekonomi Petani Kalurahan Jambidan Kapanewon Banguntapan - Zulianti Zulianti; Nelly Tiurmida (Universitas Widya Mataram, 2026)
The community of Jambidan Village, Banguntapan Subdistrict, is predominantly engaged in rice farming. Farmers apply both traditional and modern rice planting and harvesting systems. The modern system utilizes agricultural machinery (Alsintan), such as rice transplanters for planting and combine harvesters for harvesting. This study aims to analyze the social and economic impacts of Alsintan utilization on farmers and farm laborers in Jambidan Village. The research employed a descriptive qualitative method. Informants were selected using purposive sampling and further expanded through snowball sampling, resulting in six informants consisting of Alsintan users, traditional farmers, and farm laborers. Data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. Data validity was ensured using triangulation techniques. The results indicate that the use of Alsintan provides significant economic benefits for farmers by increasing efficiency in labor and production costs. For every 1,000 m² of land, farmers using Alsintan save approximately Rp250,000. However, the adoption of mechanized tools also has adverse social and economic impacts on farm laborers, particularly a reduction in employment opportunities and income. The number of laborers required decreases from 13 to 6 workers per 1,000 m² in one planting cycle, resulting in a loss of employment for seven workers. This transformation contributes to the decline of traditional rice planting and harvesting systems and affects the social conditions of rural laborers. Keywords: Alsintan; Agricultur mechanization; Farm labor; Rural society; Socio-economic change